2014
DOI: 10.1093/mnras/stu1552
|View full text |Cite
|
Sign up to set email alerts
|

Engulfing a radio pulsar: the case of PSR J1023+0038

Abstract: The binary millisecond radio pulsar PSR J1023+0038 has been recently the subject of multi-wavelength monitoring campaigns which revealed that an accretion disc has formed around the neutron star (since 2013 June). We present here the results of Xray and UV observations carried out by the Swift satellite between 2013 October and 2014 May, and of optical and NIR observations performed with the REM telescope, the Liverpool Telescope, the 2.1-m telescope at the San Pedro Mártir Observatory and the 1.52-m telescope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
76
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(84 citation statements)
references
References 47 publications
7
76
1
Order By: Relevance
“…8. NIR-optical contemporaneous SED of J1023 obtained in this work (orbital phase 0.59; blue squares); the NIR−X-rays SED of J1023 reported in Coti Zelati et al (2014) is also represented (red dots), with superimposed the fit with a model made by the companion star (red dashed line), the accretion disc (green dash-dotted line), and the shock emission powered by the NS spin-down luminosity (blue dotted line).…”
Section: Other Possible Causes: Jet Of Relativistic Particlesmentioning
confidence: 60%
See 3 more Smart Citations
“…8. NIR-optical contemporaneous SED of J1023 obtained in this work (orbital phase 0.59; blue squares); the NIR−X-rays SED of J1023 reported in Coti Zelati et al (2014) is also represented (red dots), with superimposed the fit with a model made by the companion star (red dashed line), the accretion disc (green dash-dotted line), and the shock emission powered by the NS spin-down luminosity (blue dotted line).…”
Section: Other Possible Causes: Jet Of Relativistic Particlesmentioning
confidence: 60%
“…The system has been the subject of extensive multi-wavelength campaigns after its change of state (Halpern et al 2013;Kong 2013;Linares et al 2014;Patruno et al 2014;Takata et al 2014;Tendulkar et al 2014;Coti Zelati et al 2014;Deller et al 2015;Archibald et al 2015;Bogdanov et al 2015;Shahbaz et al 2015). Radio band observations performed by Deller et al (2015), in particular, showed a rapidly variable and flat spectrum that persisted over six months.…”
Section: Psr J1023+0038mentioning
confidence: 99%
See 2 more Smart Citations
“…Swift has been used to regularly monitor the long-term behavior of PSR J1023+0038 since 2013 October (Coti Zelati et al 2014;Patruno et al 2014;Takata et al 2014). It observed the binary on 2013 November 10-13 and 2014 June 11 coincident with the XMM-Newton exposures.…”
Section: Swift Xrtmentioning
confidence: 99%